Scaling Enumerative Program Synthesis via Divide and Conquer - Alur, Rajeev; Radhakrishna, Arjun; Udupa, Abhishek (Tools and Algorithms for the Construction and Analysis of Systems (TACAS), 2017)
Given a semantic constraint specified by a logical formula, and a syntactic constraint specified by a context-free grammar, the Syntax-Guided Synthesis (SyGuS) problem is to find an expression that satisfies both the syntactic and semantic constraints. An enumerative approach to solve this problem is to systematically generate all expressions from the syntactic space with some pruning, and has proved to be surprisingly competitive in the newly started competition of SyGuS solvers. It performs well on small to medium sized benchmarks, produces succinct expressions, and has the ability to generalize from input-output examples. However, its performance degrades drastically with the size of the smallest solution. To overcome this limitation, in this paper we propose an alternative approach to solve SyGuS instances. The key idea is to employ a divide-and-conquer approach by separately enumerating (a) smaller expressions that are correct on subsets of inputs, and (b) predicates that distinguish these subsets. These expressions and predicates are then combined using decision trees to obtain an expression that is correct on all inputs. We view the problem of combining expressions and predicates as a multi-label decision tree learning problem. We propose a novel technique of associating a probability distribution over the set of labels that a sample can be labeled with. This enables us to use standard information-gain based heuristics to learn compact decision trees. We report a prototype implementation eusolver. Our tool is able to match the running times and the succinctness of solutions of both standard enumerative solver and the latest white-box solvers on most benchmarks from the SyGuS competition. In the 2016 edition of the SyGuS competition, eusolver placed first in the general track and the programming-by-examples track, and placed second in the linear integer arithmetic track.